Safety at high altitude: the importance of emotional dysregulation on pilots’ risk attitudes during flight - Luciani, Federica; Veneziani, Giorgio; Ciacchella, Chiara; Rocchi, Giulia; Reho, Matteo; Gennaro, Alessandro; Lai, Carlo (Frontiers in Psychology, 2022)
Aviation psychology is very interested in understanding how personological and psychological variables influence flight performances. Indeed, risk attitudes have been considered as a risk factor for aviation accidents. In this context, emotions and coping style are key variables which could influence concentration by affecting cognition and attention. In addition, the specific training backgrounds seemed to be associated with differences in in-flight accident rates. The aim of the present study was to investigate the association between age, sex, flight experience, emotional dysregulation, coping styles, flight licenses, and pilots’ risk attitudes. Eighty pilots completed an online survey composed of ad hoc questionnaire for sociodemographic and work-related information’s and self-report questionnaires that assessed emotional dysregulation, coping styles, and risk attitudes. Results showed that older age and emotional dysregulation were associated with higher risk attitudes in pilots. Moreover, emotional dysregulation seemed to promote worse self-confidence. Ultralight pilots appeared to be more risk-oriented and less self-confident than civil pilots, while more flight experience appeared to favorite greater self-confidence. In conclusion, the study suggests the importance of promoting interventions based on sharing pilots' difficulties and emotions and promoting safe attitudes with special attention to ultralight pilots, age, and sex differences.